Sosialisasi Pemanfaatan Aplikasi Tiktok Sebagai Media Pemasaran Modren untuk Meningkatkan Volume Penjualan Pelaku Usaha Jasa Jahit - Hyasinta Lusiana Turnip; Emilia Junidar Manalu; Yesa Estomihi Purba; Joy Vera Yohana Manik; Natalia Jesiska Purba; Hotmian Hasibuan; Rossa Aprilia Manurung; Nabilah Yafi Anis Sitorus; Kristin Dahlia Nesa Manullang; Imelda Sabrina Sibarani (Jurnal Pendidikan dan Pengabdian Masyarakat, 2026)
Microenterprises in the tailoring service sector continue to face limitations in utilizing digital media for marketing, resulting in suboptimal promotional reach and sales performance. This community service program aimed to enhance entrepreneurs' capacity to use TikTok as a digital marketing platform to expand promotional outreach and increase sales volume. The program was conducted on May 29, 2026, at Uli Kebaya Tailoring Service, Pematang Raya Market, Simalungun Regency, employing a Participatory Action Research (PAR) approach. The activities included educational sessions, demonstrations on TikTok utilization, hands-on assistance in developing promotional content, and a 28-day self-evaluation period from May 30 to June 26, 2026. The results demonstrated that the business owner successfully managed the TikTok account independently and consistently uploaded six promotional videos during the mentoring period. These videos generated a total of 27,860 views, 823 likes, 39 comments, 129 saves, and 19 shares. Throughout the evaluation period, the TikTok account achieved 97,900 total views and approximately 3,000 likes, with most audience reach originating from the For You Page (FYP) feature, indicating the effectiveness of organic content distribution. In addition to improving the participant's digital marketing competencies, the implementation of TikTok also produced an initial business impact, evidenced by the acquisition of two new customers following account activation. These findings suggest that practice-based training combined with continuous mentoring is effective in strengthening the digital marketing capabilities of micro-enterprise owners while creating opportunities for broader market expansion.